2014
DOI: 10.5296/jsss.v2i1.6843
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Body Image Satisfaction and Psychological Well-Being: The Impact of Africentric Values

Abstract: Empirical studies established a link between body image measured as body mass index and psychological variables in western cultures with less inclusion of indigenous Africans. The present study investigated the influence of body image satisfaction on the psychological well-being of individuals within the African cultural context. Body image dimension was redefined and expanded to include four other components: facial appearance, appendage appearance, physical appearance, and complexion and body mass index. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
5
12
0
Order By: Relevance
“…The results of the Pearson correlation coefficient showed a significant positive relationship between psychological wellbeing and body image. The results of this study regarding the relationship between psychological wellbeing and body image is in agreement with that of the studies by Dotse,[ 14 ] Jane Sabik,[ 18 ] and Winefiel et al . [ 19 ]…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of the Pearson correlation coefficient showed a significant positive relationship between psychological wellbeing and body image. The results of this study regarding the relationship between psychological wellbeing and body image is in agreement with that of the studies by Dotse,[ 14 ] Jane Sabik,[ 18 ] and Winefiel et al . [ 19 ]…”
Section: Discussionsupporting
confidence: 93%
“…Self-acceptance is a perception that provides individuals with awareness of their strengths and weaknesses and a realistic view of their abilities, through which and by the development and improvement of their activities, they can achieve a positive view of themselves. [ 14 ] Pregnancy is most often considered as a strength which will result in the reinforcement of the sense of femininity and self-acceptance [ 24 ] that can result in body image satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study found a prevalence of individuals at risk for exercise dependence (9.9%) which is comparable to previous research conducted in sports and exercise settings [ 32 , 70 , 85 , 86 ], while being higher than in studies conducted on larger “normal” populations, for example, representative populations for one country [ 44 , 87 ]. Furthermore, cultural and national differences have also been reported to play a role in terms of prevalence of exercise dependence [ 85 ] as well as self-esteem and the cultural emphasis on appearance and body shape [ 88 , 89 ], which must be taken into consideration when comparing our study to others.…”
Section: Discussionmentioning
confidence: 99%